Al Jarh wa At-Ta'dil in Researching Sanad Hadits - Widodo, Heru; Irfanudin, Fahmi (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2020)
In Islam, the hadith has apposition as the number two source of Islamic law after the Qur'an. However, not all hadiths can be used immediately. There are hadiths that are not used as a legal basis, because after investigation, it turns out that certain hadiths do not originate from the Prophet Muhammad PBUH. Using a literature survey, this article found that the science of Jarh wa ta'dil is a science used to find out the negative and positive nature of the narrators of the hadith which has an influence on the quality of the narration that was narrated. By mastering the science of jarh wa ta'dil, it can select which hadiths are authentic and which are not valid, especially in terms of the quality of the narrators of the hadith, not in terms of obedience. There are several methods that have been studied and determined by the scholars in explaining the narrators' narration of the hadith, both in a defective state and in a tsiqah state. Among these are: Honesty in providing judgments, careful in researching and evaluating someone, paying attention to ethics and manners in the jarh, and mentioning the causes of disability or weakness of narrators of the hadith. The scholars of jarh wa ta'dil disagree regarding the statements of the problem of jarh wa ta'dil regarding their assesment of narrators of the hadith. Some scholars give a negative value and some others rate positively. If for example it happens in such a way, then further research is needed that is more directed to the truth. In examining the hadith, especially regarding the character of the narrators of the hadith, it is obligatory to refer to several references, so that the results of the research can be objective. Therefore, this article recommends further research, specifically how to implement the theory of jarh wa ta'dil in determining good leaders in this globalization era.